A Study of Market Scenario of Sand Stone Industry of Rajasthan (International Journal of Food and Nutritional Sciences, 2022)
India possesses a wide spectrum of dimensional stones that include granite, marble, sandstone, limestone, slate, and quartzite, in various parts of the country. The stone industry in India has evolved into the production and manufacturing of blocks, flooring slabs, structural slabs, monuments, tomb stones, sculptures, cobbles, pebbles and landscape garden stone. In the Rs 60,000-crore stone industry of the country, Rajasthan is a leading player occupying over 30% of the business. While exports constitute about 35% of the total production, revenues from the domestic market is a big driver. High exports growth has come off in the past 4-5 years. But there was still some growth although it was marginal. But now, this will also be wiped out. As per the latest reports by CAPEXIL (Export Promotion Council for Stones), exports from India in 2017-18 stood at $1,939 million and Dhoot estimates the growth in the past couple of years to be in lower single digits. As per Volza’s India Export data, Stone export shipments from India stood at 2.5M, exported by 35,469. The main purpose of the article is to study the market scenario of Sand Stone Industry in Rajasthan.